DIELECTRIC PROPERTIES OF BLOOD OF PULMONARY TUBERCULOSIS PATIENTS - N. MANOHAR REDDY, (International Journal of Pharma and Bio Sciences, 2016)
The objective of the research is to study the dielectric properties of blood of pulmonary tuberculosis patients. The parameters such as dielectric constant, dielectric loss and electrical conductivity are measured at the frequency of 1 KHz. In this paper a conductivity meter (Elico, CM 183) was used in the present investigation. The accuracy of conductivity measurement is ±1%.The dielectric properties such as dielectric constant, dielectric loss were determined at the frequency of 1 kHz, using the digital LCZ meter of tuberculosis patient’s blood. It is observed that the values of dielectric constant, dielectric loss are very high and electrical conductivity is slightly low in tuberculosis blood, compared with normal blood. It is believed that the findings of this study may be useful as indicators of disease progression, cardiovascular risk factors and response to therapy in pulmonary tuberculosis patients.